Spectrophotometric determination of acetazolamide using a flow injection system with KMnO4 reagent - Almeida, Maria G.J. [UNESP]; Teixeira, Marcos F.S. [UNESP]; Marques Gomes, Homero [UNESP] (My University, 2012)
A flow injection spectrophotometric method was developed for the determination of acetazolamide, (N-(5-sulfamoyl-1,3,4-thiadiazol-2-yl)acetamide), in commercial anti-hypertensive drugs. The new and simple procedure is based on the reaction between sulfonamide groups and permanganate ions in an alkaline medium. The results showed that linear quantification of acetazolamide could be achieved at two wavelengths. A decrease of the permanganate concentration could be measured at 530 nm, while an increase in manganate concentration could be measured at 610 nm, in the concentration ranges from 1.0 × 10-5 to 2.5 × 10-4 mol L-1 and from 2.5 × 10-5 to 2.5 × 10-4 mol L-1, respectively. The detection limits were 4.5 × 10-6 mol L-1 (530 nm) and 2.2 × 10-6 mol L-1 (610 nm). The usual excipients used in commercial drugs did not interfere in the determinations, and the results were consistent with those obtained by a UV reference technique.
Keywords: Acetazolamide; Flow injection; Permanganate; Spectrophotometric determination